THE PRACTICE OF DIGITALIZATION OF INNOVATIVE TOURIST ROUTES IN ZOMIN DISTRICT OF JIZZAKH REGION - Ergashov Y.S.; Otamurodov G.R. (International Scientific and Current Research Conferences, 2024)
This study explores the practice of digitalization of innovative tourist routes in the Zomin district of the Jizzakh region, Uzbekistan. By developing a mobile application and utilizing GIS technology, the project enhances visitor experiences and accessibility to cultural and natural attractions. Results indicate a significant increase in tourist engagement and local business patronage, with user satisfaction rates reaching 85%. The findings underscore the economic and cultural benefits of digitalization while highlighting challenges such as internet connectivity. Continued investment in technology and community training is essential for sustainable tourism development in Zomin, promoting both economic growth and cultural preservation.